A new deepwater gurnard of the genus Pterygotrigla (Scorpaeniformes: Triglidae) from the southwestern Indian Ocean - Yato, Takuji; Heemstra, Elaine (Zootaxa, 2019)
A new species of deepwater gurnard, Pterygotrigla (Otohime) madagascarensis sp. nov. is described, based on two specimens collected on the upper continental slope south of Madagascar, in the southwestern Indian Ocean. The new species belongs to the tropical Indo-Pacific subgenus Otohime in having a short rostral projection, short posttemporal spine, long opercular spine and no cleithral spine. It is most similar to P. (O.) multipunctata, and P. (O.) urashimai, in having no large blotch on the first dorsal fin, a jet-black blotch and no white ocellus on the inner pectoral-fin surface, with no scales on the breast and front of the pectoral-fin base. However, the new species differs from the latter two species by the combination of the following characters: first dorsal-fin spines 7, second dorsal-fin rays 12, dusky rays on the inner pectoral-fin surface, one row of blackish botches on second dorsal fin, and no papillae on the dorsal surface of oral cavity. A key is provided for the twelve Pterygotrigla species now in the subgenus Otohime.